PERSOALAN METODE KUANTITATIF DAN KUALITATIF - Mochamad Syawie (Sosio Informa, 2005)
(The Problem of Quantitatif and Quality Method) - Sebuah Kajian Sosiologis. Two perspective in sosiology, and the each has the big influence for methodology. The first, usually we mention positivistic (positivism), and the second is humanistic (humanism) perspective. Positivistic perspective influence to idealism to be sosiology as knowledge sciences as natural sciences. This condition refer to conviction that indications social submission with natural law as determenistik character. The opposite, although the humanistic perspective interest with sosiology as knowledge sciences, but the perspective is different with natural sciences. So the regulation of natural indication can't explain about humanity behavior. That different perspective, caused theory and methodology differencies. For positivistic perspective, the theory explain about correlation inter social indications, as with subjectif characteristic from individual be ignored. The opposite in humanistic perspektif, theory interpret the meaning and purposed about social indications, with attention from subject as focused.